Implementation of the Altman z-score model in predicting bankruptcy at PT. Garuda Indonesia, Tbk. - Sriwiyanti, Eva; Purba, Djuli Sjafei; Wahyudi, Dendi; Tarigan, Wico Jontarudi; Napitu, Resna (Journal of Accounting and Investment, 2024)
Research aims: This study aims to forecast Garuda Indonesia’s bankruptcy rate using the Altman Z-Score model analysis tool based on financial statement data for the 2012-2021 period.Design/Methodology/Approach: A quantitative description method was used, with data sources from the Garuda Indonesia website.Research findings: Based on the data analysis, Garuda Indonesia was in a "gray area" or financial difficulty in the overall observation year.Theoretical contribution/Originality: Since 2020, Garuda Indonesia has implemented a statement of financial accounting standards (PSAK 73) on lease regulations. According to Institute of Indonesia Chartered Accountants (IAI, 2022), the objective of PSAK 73 on leases is to determine the principles for recognizing, measuring, presenting, and disclosing leases and determine whether the lessee and lessor provide relevant data with a method that presents transactions appropriately. PSAK 73 on leases categorizes assets from finance leases designated as right-of-use assets as part of property, plant, and equipment and lease liabilities as part of long-term liabilities that appear in the statement of financial position. Following the Institute of Indonesia Chartered Accountants (2022), right-of-use assets describe the tenant's right to use assets granted by the lessor to the lessee during the lease term.Research limitation/Implication: This research has limitations since the reference sources only came from research journals conducted at manufacturing and service companies in Indonesia and researched by Indonesian researchers. The data studied was only for the last 10 years (2012-2021) and during that time the 2019 Covid pandemic occurred, resulting in a lockdown which caused the number of domestic and international flights to Indonesia to decrease drastically.